PERILAKU MASYARAKAT DALAM MENGGUNAKAN MEDIA DIGITAL DI MASA PANDEMI - Apdillah, Dicky; Deri, Afif; Wijaya, Chandra Ridho; Sitorus, Muhammad Aldi Prayuda (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2022)
Indonesia is one of the countries affected by the Covid-19 outbreak. PolicyThe government regarding Large-Scale Social Restrictions (PSBB) has an impact on various sectors in Indonesia, be it the economic, entertainment, religious and education sectors. The need for understanding the use of digital media in the community will determine the mindset of the community in dealing with this pandemic. Educational activities that were stopped during the pandemic have been transformed into online learning by utilizing digital media. Ease of accessing all information through several applications in gadgets in people's lives, but not all people take advantage of these opportunities positively. The purpose of this study was to determine people's behavior in using digital media during the Covid-19 pandemic. The research method used is a literature review method based on literature exploration from the results of previous studies. These literatures are in the form of books, survey results, online media, and national research articles. The results of the study revealed that there were major changes in people's behavior in several aspects. The changes come from their own initiative as well as an appeal or order from the competent authority. In addition, the pandemic period affects people's mental and psychological health. Media has always been a social institution, during this pandemic, learning can be carried out using various platforms, both in the form of a learning management system and in the form of video conferencing so that parents and teachers are required to have digital literacy skills. The conclusion of the study is that the use of digital media greatly influences people's behavior, besides the ability to use digital media is needed by the community as a digital literacy effort during the Covid-19 pandemic.